Sejarah Dinasti Abbassiyah dan Perkembangan Pendidikan Islam Masa Modern - Salsabila, Rosanti (ALSYS, 2021)
This study aims to find out various issues ranging from the history of the establishment of the Abbassid dynasty to the development of modern Islamic education, the Islamic world again reached its peak of glory during the reign of the Abbasid Daula which was centered in Baghdad, five and a half centuries since its establishment in 132 H (750 AD). until the destruction of Baghdad by Hulagu Khan in 1268 AD (656 H). The sovereignty of the Muslims in this era has reached the peak of glory, both wealth, progress, or power. Even in this era, various Islamic sciences have been born and developed and various important sciences have been translated into Arabic. It seems that reforming ideas about the education system always get the attention of every reformer thinker. This is because education is an arena of study that never runs dry, because the main problem being discussed is about humans and all their aspects. In addition, the way to achieve the goal of thinking is done, both through formal and non-formal education.